IMPLEMENTASI EFISIENSI DAN SAFETY PENGGUNAAN LISTRIK DI YAYASAN AL AMIN SIDOMULYO (YAAS) DESA SIDOMULYO KECAMATAN ADIMULYO KABUPATEN KEBUMEN - Syahid Syahid; Sidiq Syamsul H; Ari Santoso (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Electricity consumption in Indonesia in recent years has increased 10- 15% per year. There was an increase in electricity in the household sector, from about 24,000 SBM (Unit Barrels Oil) in 1999 to 33,000 SBM in 2003. Accident that caused electricity is also very large due to electrical problems. The potential of energy conservation and safety of electrical energy usage in all sectors has a considerable opportunity of raising. Yayasan Al Amin Sidomulyo is one of the foundations that have various activities such as education field of KBIT, TKIT, madrasah, boarding school, agriculture, hajj guidance, cooperative and community empowerment located in Kebumen district. The use of electrical appliances such as  Refrigerator, Dispenser, Rice Cooker in addition to lights become a major contributor to energy consumption. The increase in Basic Electricity Tarif (TDL) will further increase the expenditure of electricity payments. The board and students in the Foundation are also a problem in terms of electrical safety. Often managers or children do not know and do not deliberately hold or contact with electricity that is very dangerous. The result of this community service is contributing to solving problems in the field of energy efficiency and safety of electrical energy usage for the Foundation. The specific target of this Service is (1) electrical energy efficiency; (2) safety of electrical energy usage. Keywords: The foundation of Al Amin Sidomulyo, Energy Efficiency, Safety, Electrical Energy